Transmitting Al Ardha: Traditional Arab Sword Dance. Issue 1 (March 2015) - Khan, Muqeem
There is a knowledge deficit about Al Ardha dance movements in Gulf Arab culture, and the dance form is not yet analytically documented. This paper is the first attempt to explain and isolate some of the thought processes related to this indigenous festive activity in the Arabian Peninsula. The study conceptualizes the dance in a manner conducive to its transfer to a digital learning environment designed for user interaction. Aimed at developing a motion detection-based kinesthetic learning system, this study also tries to identify the motor and cognitive skills related to the Al Ardha dance. The anticipated system can provide tremendous opportunities for users to learn the dance-related harmonious movements without the help of a live instructor. The study can also help identify and isolate some of the predominant movements of this dance to investigate its analytical paradigm.